Matematyka
andrzejowyandrzej
2021-01-17 19:11:27
(-4,5)*5/9+(-6,4)*3/2   =                             3          2 (1 1/3)   * [2,7*4/9-3]=
Odpowiedź
lorenz
2021-01-17 22:16:01

(-4.5) *5/9 +(-6,4) *3/2^3 = (-45/10) *5/9 +(-64/10) *27/8 = ( -5/2) *1/1 + (-8/10 ) * 27/1 = (-5/2) +(-216/10) = (-25/10 ) +(-216/10) = 240/10 = 24 (1i1/3)^2 *[ 2,7 *4/9 -3] = (4/3)^2 *[27/10 *4/9 -3] = 16/9 *[3/5 * 2/1 -3] =   = 16/9 * [ 6/5 -3 ] = 16/9 *[6/5 - 15/5) = 16/9 *[-9/5] = 16/1 *[-1/5] = -16/5 = -3i1/5

Dodaj swoją odpowiedź